Improving patient access through office hysteroscopy clinic redesign - Wygant, Jenna N; Laughlin-Tommaso, Shannon K; Green, Isabel C; Price, Kelly R; Burnett, Tatnai L; Hopkins, Matthew R; Famuyide, Amimbola O; Breitkopf, Daniel M (Journal of the American Association of Nurse Practitioners, 2020)
Patients with abnormal uterine bleeding (AUB) often require hysteroscopy as part of the diagnostic workup. The purpose of this study was to improve efficiency by shortening the time to patient appointment for office hysteroscopy. Preintervention, nurse practitioners (NPs) and gynecologists saw patients with abnormal uterine bleeding (AUB) separately. This created inefficiency for the patients, frequently requiring second visits for hysteroscopy. A new hysteroscopy clinic was designed to increase practice efficiency. A collaborative team model was created including consecutive visits with NPs and gynecologists. Each patient with AUB was first evaluated by an NP, followed immediately by a shorter visit with a gynecologist for office hysteroscopy as indicated. NPs managed other diagnostic evaluation and bleeding treatment if hysteroscopy was not warranted. Collaborative clinic staffing consisted of two NPs seeing patients with AUB paired with one gynecologist for procedural support. Electronic records of 393 patients scheduled for AUB visits from January to June 2015 were evaluated for preintervention data. Postintervention, 647 patient records were reviewed from January to June of 2016. During the preintervention period, 30% of patients had a hysteroscopy appointment scheduled within 0-13 days from the initial visit for AUB. Postintervention, the wait time for appointments decreased, with 63% of patients scheduled within 0-13 days. Clinic redesign also resulted in an increase of 57.5% in appointment slots. No-show rates and appointment fill rates were not adversely affected. A collaborative team-based care model using NPs and gynecologists improved efficiency and access to office hysteroscopy services.